2021
DOI: 10.48550/arxiv.2107.00770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypergeometric Multiple Orthogonal Polynomials and Random Walks

Amílcar Branquinho,
Juan E. Fernández-Díaz,
Ana Foulquié-Moreno
et al.

Abstract: A. The recently found hypergeometric multiple orthogonal polynomials on the step-line by Lima and Loureiro are shown to be random walk polynomials. It is proven that the corresponding Jacobi matrix and its transpose, which are nonnegative matrices and describe higher recurrence relations, can be normalized to two stochastic matrices, dual to each other. Using the Christo el-Darboux formula on the step-line and the Poincaré theory for non-homogeneous recurrence relations it is proven that both stochastic matric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Notice that in [2] this was taken as granted, and that in the hypergeometric case [29,3] and the Jacobi-Piñeiro in the semi-band [2,5] is also true that 𝛼 2 > 0. This motivates the following notion:…”
Section: R Hmentioning
confidence: 99%
See 2 more Smart Citations
“…Notice that in [2] this was taken as granted, and that in the hypergeometric case [29,3] and the Jacobi-Piñeiro in the semi-band [2,5] is also true that 𝛼 2 > 0. This motivates the following notion:…”
Section: R Hmentioning
confidence: 99%
“…𝑁+1 of the auxiliary matrix T [𝑁] satisfy B [1] 𝑁+1 𝜆 [𝑁] 𝑛 = 𝐵 [1] 𝑁+1 𝜆 [𝑁] 𝑛 + 𝛼 2 𝐵 [2] 𝑁+1 𝜆 [𝑁] 𝑛 , B [2] 𝑁+1 (𝜆 [𝑁] 𝑛 ) = 𝐵 [2] 𝑁+1 𝜆 [𝑁] 𝑛 + 𝛼 5 𝐵 [3] 𝑁+1 𝜆 [𝑁] 𝑛 , . .…”
Section: Lemma 7 the Polynomials B[𝑘]mentioning
confidence: 99%
See 1 more Smart Citation
“…This paper is devoted to the study of multiple orthogonal polynomials with two weights on the step-line. In the research on the relation between Markov chains beyond birth and death processes and multiple orthogonal polynomials [9,10] we get, as a byproduct, some results that hold for families of these type I and II simple cases. Moreover, in order to better understand some of these phenomena we turned back to the definition of multiple orthogonality and find, to the best of our knowledge, some unknown facts so far.…”
mentioning
confidence: 94%
“…It is also shown that the type I linear form associated to the sequence of type II multiple orthogonal polynomials {𝐵 (𝑛) } ∞ 𝑛=0 is also uniquely determined. Examples of this gauge freedom with almost uniform Jacobi matrices are obtained in [10].…”
mentioning
confidence: 99%